Etymological Experiments and Corrections - ZAKARYAN, HOVHANNES (Bulletin of Yerevan University B: Philology, 2021)
The present article, proceeding from morpho-semantic analyses and analyses of linguistic universals, offers to derive a number of Armenian words, still not etymologized or considered to be borrowings, from PIE root *smē- (*smeī-, *sm-ei-) "to smear, rub" and its derivative variants (extended by root determinatives and framed by different ablaut steps). They are: մերսել "massage" [<*mer-k՚-], մարզել "to train" [<*mŗ-g՛h-], մաշտել "scrape off" [<*(s)mǝ(r)-s-], մշտել "poke" [<*(s)mō(r)-s-], մարմանդ "mild" [<*(s)mǝr-m-], մրափ "slumber" [<*(s)mōr-], մզել "squeeze" [<*(s)mō-(r)-g՛h-], մերժել "reject" [<*(s)mer-gwh-] etc.